THE DEVELOPMENT OF INTERCULTURAL COMMUNICATIVE COMPETENCE IN ENGLISH FOR TOURISM: A NEED ANALYSIS - IGAP Novita Sari Paragae (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2023)
This study aimed at investigating teachers’ and students’ perception on the development of intercultural communicative competence in English for Tourism subjects and the dimension which is perceived to be needed the most. The study was conducted in the form of descriptive study. Five English teachers and twenty-five students who were joining training programs in hotels were chosen as subjects. The data were collected by using questionnaires and interview. The result showed that both students are teachers perceived that intercultural communicative competence is strongly needed in English tourism class. It was also revealed that among three dimensions of ICC, skill is placed in the first place due to its importance, followed by attitude and knowledge. Thus, this study give implication to the curriculum development to insert intercultural communicative competence to be the additional goal of the English lesson since it is needed by the students in to develop their professional competence in tourism industry.